2005
DOI: 10.1088/0953-2048/19/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Flux transistor made from a single-layer niobium thin-film superconducting quantum interference device

Abstract: A micrometre-size Josephson vortex flow transistor is demonstrated experimentally. The drain-source of this device is the output of a single-layer Nb superconducting quantum interference device (SQUID) with a nanometre-size hole, forming a nanoSQUID. The device input is a Nb strip, which is closely coupled to the nanoSQUID. The change of the input current induces a change in the magnetic flux coupling to the nanoSQUID, and hence modulates the current-voltage characteristics of the nanoSQUID. The current gain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In this framework, the nanoSQUID have been proposed as a flux flow transistor [278] and trapped-vortex memory device [278]. As regard as the transistor, Lam [279] demonstrated that a Josephson nanodevice, including a nanoSQUID (similar to that shown in Fig. 21) and a single Nb strip, can acts as a gate and employed as three-terminal device (Fig.…”
Section: Nanoelectronics and Quantum Computingmentioning
confidence: 99%
“…In this framework, the nanoSQUID have been proposed as a flux flow transistor [278] and trapped-vortex memory device [278]. As regard as the transistor, Lam [279] demonstrated that a Josephson nanodevice, including a nanoSQUID (similar to that shown in Fig. 21) and a single Nb strip, can acts as a gate and employed as three-terminal device (Fig.…”
Section: Nanoelectronics and Quantum Computingmentioning
confidence: 99%
“…In order to minimize the required write current, the Nb strip has to be close to the nanoSQUID. Our previous work indicates that a write current of less than 200 μA can couple a magnetic flux of ∼0.5 o into the nanoSQUID, a very promising result [22].…”
Section: Hysteretic Behaviour In Nanosquidsmentioning
confidence: 98%
“…For a practical memory cell, a control line would be used to manipulate the flux state of each cell. This can be achieved by using a Nb strip patterned closely to the nanoSQUID [18,22]. In order to minimize the required write current, the Nb strip has to be close to the nanoSQUID.…”
Section: Hysteretic Behaviour In Nanosquidsmentioning
confidence: 99%
“…There has been some development of various three-terminal devices based on nanoSQUIDs in both all Nb [31] and hybrid Nb-carbon nanotubes [9]. The hybrid carbon nanotube threeterminal device uses gate-tunable carbon nanotubes (CNTs) for the Josephson junctions.…”
Section: Nanoelectronics Including Memorymentioning
confidence: 99%